2018
DOI: 10.26699/jnk.v5i2.art.p144-149
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Penggunaan Sosial Media dan Pengetahuan Seks Bebas pada Siswa/Siswi Usia 17-18 Tahun

Abstract: Many factors can affect teen sex knowledge (Students,) one of them is information media such as the social media. The purpose of this study was to determine the correlation of facebook and instagram usage with free sex knowledge of 17-18 years old students of senior high school PGRI TALUN Blitar. This design of the study was Corelational with Cross sectional design. The population in this study was all of students aged 17-18 years old of senior high school PGRI TALUN Blitar. The sample was 28 students. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Interventions in the digital era of adolescent reproductive health are diverse, ranging from social media (23)(24)(25)(26)(27)(28) and healthcare applications to gaming models (28,29). The interventions in this study lasted from 10 days to a year, with one conducted through Instagram posts( 30) and ( 29) over 10 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions in the digital era of adolescent reproductive health are diverse, ranging from social media (23)(24)(25)(26)(27)(28) and healthcare applications to gaming models (28,29). The interventions in this study lasted from 10 days to a year, with one conducted through Instagram posts( 30) and ( 29) over 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…A review of 21studies showed, 90.4% of the studies showed an increase in knowledge, attitudes, or behavior toward providing reproductive health education to adolescents, while 9.6 considered that the internet still presented a contradictory perspective and provided a cultural shift (17,20). The results showed that 85.7% of adolescents used the social media sites Facebook and Instagram, of which 71.4% and 10.7% had a good and sufficient level of knowledge, respectively (23). Social media was found to be a very effective medium for adolescents in citie,s but not for those in rural areas (17).…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…Jejaring sosial tersebut selain membawa manfaat positif juga membawa dampak negatif bagi remaja. Manfaat positifnya selain mempererat tali silaturahmi juga bisa mendapatkan informasi terbaru dari status orang lain sedangkan dampak negatifnya yaitu dapat mengganggu privasi, membuat ketagihan sehingga dapat mengganggu waktu untuk belajar dan dapat mempengaruhi para remaja untuk melakukan seks bebas (Wahyuningtias & Wibisono, 2018 (Pinem, 2009). Konten pornografi bisa masuk dikarenakan banyak layanan jejaring sosial yang menyediakan kumpulan cara yang beragam bagi pengguna untuk dapat berinteraksi seperti chat, messaging, email, video, share file, blog, diskusi grup, dan lainlain.…”
Section: Sumber Informasiunclassified
“…Selain itu, ada hubungan yang kuat antara penggunnan media sosial facebook dan instagram dengan pengetahuan remaja tentang seks bebas remaja di tandai nilai r sebesar 0,666. Hal ini mengindikasikan penggunaan media sosial merupakan salah satu sumber untuk mendapatkan pengetahuan remaja tentang seks bebas (17). Selain itu penelitian ini sejalan dengan penelitian Anissa dan Nunik (2017) dimana dengan hasil analisis Chi Square menghasilkan nilai signifikansi sebesar 0,000 ( p < α = 0,05), artinya terdapat hubungan antara sikap pengendalian diri dalam penggunaan media jejaring sosial facebook terhadap perilaku seksual pranikah pada remaja usia 15 sampai 19 tahun (18).…”
Section: Penggunaan Media Mempengaruhi Niatan Siswa Untuk Mencegah Pe...unclassified